Difference and disability in the medieval Islamic world : blighted bodies - Richardson, Kristina L. (Edinburgh : Edinburgh University Press, 2012)
Outlines the complex significance of bodies in the late Medieval central Arab Islamic lands. Did you know that blue eyes, baldness, bad breath and boils were all considered bodily 'blights' by Medieval Arabs, as were cross eyes, lameness and deafness? What assumptions about bodies influenced this particular vision of physical difference? How did blighted people view their own bodies? Through close analyses of anecdotes, personal letters, biographies and autobiographies, erotic poetry, non-binding legal opinions, diaristic chronicles and theological tracts, Kristina Richardson brings the cultural views and experiences of disability and difference in the medieval Islamic world to life. This title investigates the place of physically different, disabled and ill individuals in medieval Islam. It is organised around the lives and works of 6 Muslim men, each highlighting a different aspect of bodily difference. It addresses broad cultural questions relating to social class, religious orthodoxy, moral reputation, drug use, male homoeroticism and self-representation in the public sphere. It moves towards a coherent theory of medieval disability and bodily aesthetics in Islamic cultural traditions.
Based on author's dissertation.
Includes bibliographical references (p. 138-156) and index.
Keywords: Sociology of disability -- Middle East -- History -- To 1500.; Disabilities -- Social aspects -- Middle East -- To 1500.